A Potential Biomarker of Combination of Tumor Mutation Burden and Copy Number Alteration for Efficacy of Immunotherapy in KRAS-Mutant Advanced Lung Adenocarcinoma - Xiang, Luochengling; Fu, Xiao; Wang, Xiao; Li, Wenyuan; Zheng, Xiaoqiang; Nan, Kejun; Tian, Tao (Frontiers in Oncology, 2020)
Objectives The Kirsten Rat Sarcoma (KRAS) mutation is the commonest oncogenic drive mutation in lung adenocarcinoma (LUAD) and immunotherapy may be quite promising for KRAS-mutant LUAD. While the effects of tumor mutation burden (TMB) and copy number alteration (CNA) are poorly understood in this illness, our study aimed to explore the roles TMB and CNA play in the prediction of response to immune checkpoint inhibitor (ICI) therapy in advanced KRAS-mutant LUAD. Methods Mutation and clinical data were downloaded from cBioPortal. We evaluated KRAS mutation status and divided patients into different subgroups based on TMB and CNA cutoffs to investigate the predictive value of these biomarkers on ICI response. Results KRAS mutation with concurrent TP53 or STK11 mutations had higher TMB and CNA compared to KRAS mutation alone. The KRAS G12C and G > T mutation subgroups, with TP53 or STK11 co-mutation, also had higher TMB and CNA. We found that TMB and CNA were independently associated with progression-free survival (PFS) and durable clinical benefits (DCB); TMB was positively correlated with PFS (P = 0.0074) and DCB (P = 0.0008) while low CNA was associated with prolonged PFS (P = 0.0060) and DCB (P = 0.0018). However, TMB alone did not distinguish benefits among KRAS-mutant patients. Notably, when combining TMB and CNA, low TMB and high CNA revealed worse outcomes of ICI therapy (mPFS: 2.20m, P = 0.0023; proportion of DCB: 24%, P = 0.0001). Conclusion The combination of TMB and CNA provides more sensible and accurate prediction of ICI response than individual factors in KRAS-mutant LUAD. Moreover, low TMB and high CNA can be utilized as a potential biomarker to predict adverse outcome in KRAS-mutant LUAD.